2017
DOI: 10.5812/semj.14316
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Knowledge About Clinical Importance and Effective Teaching Methods of Anatomy

Abstract: Background: Anatomy is taught to medical students during first and second years of study and there is a big interval between learning the theory and its usage in the clinic. Objectives: The aim of this study was to evaluate medical students knowledge about clinical importance and effective teaching methods of anatomy. Methods: This cross-sectional study was carried out on 225 preclinical and clinical medical students from the city of Zahedan, Iran, during October 2015 to April 2016. Participants were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…In the present study there was a minimal improvement in the mean of post -test scores of students, this can be attributed to it being formative and hence required motivation on the part of the students to utilize the opportunity provided to them,it may also be due to the amount of time allotted was not sufficient whereas students in the clinical years studied mostly for improvingtheir clinical knowledge [24].…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study there was a minimal improvement in the mean of post -test scores of students, this can be attributed to it being formative and hence required motivation on the part of the students to utilize the opportunity provided to them,it may also be due to the amount of time allotted was not sufficient whereas students in the clinical years studied mostly for improvingtheir clinical knowledge [24].…”
Section: Discussioncontrasting
confidence: 55%
“…This could be a reflection of the fact that lectures are indispensable in higher education [ 35 ]. An Iranian cross sectional study evaluated the knowledge of 225 preclinical and clinical students on the methods of teaching anatomy and they too found that lectures were perceived to be the most effective instructional method [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of students' reactive anxiety, depending on the specifics of the studied program, is primarily associated with the features of teaching anatomy at these faculties, with varying degrees of program complexity and, accordingly, with different requirements for knowledge control [26]. This biomedical discipline is the most significant for students of the medical and pediatric faculties, who need to master in details large amounts of information on the whole organism's structure and to gain practical skills.…”
Section: -Discussionmentioning
confidence: 99%